Printing on Particles Combining Two-Photon Nanolithography and Capillary Assembly to Fabricate Multimaterial Microstructures - van Kesteren, Steven (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.